Simultaneous co-saccharification and fermentation of sago hampas for bioethanol production - Micky, Vincent; Empina, Jabang; Norizawati, Muhamad Nur; Ennry, Esut; Leo, Bulin Unting; Dayang Salwani, Awang Adeni (International Commission of Agricultural and Biosystems Engineering, 2015)
Abundance of lignocellulosic biomass provides a good solution to the demands of energy crops in producing biofuel like biodiesel and bioethanol. In this study, bioethanol was produced from sago hampas via the Simultaneous co-Saccharification and Fermentation (Sc-SF) process, at 2.5% and 5.0% (w/v) solid loadings. The processing step in Sc-SF is virtually similar to that of Simultaneous Saccharification and Fermentation (SSF). However, during Sc-SF, two enzymes, amylase and cellulose, were added for the co-saccharification of sago starch and fiber. In addition, Saccharomyces cerevisiae was used to ferment the sugars in the hydrolysates. The Sc-SF samples were analyzed for carbohydrate residues, ethanol and acetic acid using the dinitrosalicylic (DNS) acid assay and High Performance Liquid Chromatography (HPLC).Results showed that the Sc-SF of the sago hampas showed high efficiencies of hydrolysis and ethanol production within the first six hours of fermentation. Highest glucose production was at 37.86 g/l for the 5.0% sago hampas load and 17.47 g/l for 2.5% sago hampas load. The highest ethanol production was observed in the broth with 5.0% sago hampas, with a theoretical yield of 80.50%. Meanwhile, the highest bioethanol yield in the sample with 2.5% sago hampas was 73.19%. This study indicated that bioethanol production via Sc-SF from starch rich agricultural residues such as sago hampas is feasible.